Zabił, nie zabił i kto kogo zabił? O filmie Zabicie ciotki Grzegorza Królikiewicza - Dondzik , Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The subject of this article is an analysis of the film Killing Auntie (Zabicie ciotki, 1984) by Grzegorz Krolikiewicz. The author reconstructs the history of the film’s making, recalls the memories of actor Robert Herubin, cinematographer Krzysztof Ptak, and director Grzegorz Krolikiewicz. The author reads Killing Auntie through the prism of Andrzej Bursa’s prose, refers to the heritage of surrealism and the way the director refers to it. According to the author it is important to answer the question of whether Killing Auntie is a specific kind of performance. The article concludes with a reflection on the moral dimension of Killing Auntie and an attempt to answer the questions: did the murder in Killing Auntie really happen and could any of us commit it?